PERENCANAAN PENGAJARAN DALAM KEGIATAN PEMBELAJAAN - Ergawati Ergawati; Ibnu Affan; Teuku Zulfahmi; Cut Liesmaniar; Iis Marsithah; Sri Milfayetty (JGK (Jurnal Guru Kita), 2023)
Teaching Planning in Learning Activities. This discussion discusses how the stages of implementing learning activities. Seeing how the implications of teaching planning in learning activities. This research method was carried out by library research with a pedagogic approach. The research results yielded two important points in the implementation of learning planning. First, preparation in planning learning activities. This activity includes looking at the characteristics and conditions that surround students, understanding the characteristics of students, understanding learning styles and abilities, and teacher competencies. Second, activities in teaching planning, including developing syllabus and preparing Learning Implementation Plans (RPP) in the implementation of teaching and learning activities. Implementation of planning activities in teaching activities that interact with the activities of how teachers teach and how students learn. This teaching activity is realized in planning. In the implementation of learning activities contain three important things, namely planning, implementation and evaluation, as well as teaching. The teacher should make preparations before carrying out the learning process. Teachers are expected to have maximum planning in learning activities and be able to provide results in improving the quality and quality of learning.